The privation theory of evil and the evil-God challenge - Collins, John M. (Religious studies, 2026)
Can the best arguments for a privation theory of evil be parodied, with equal plausibility, as arguments for a privation theory of good? The privation theory of evil claims that evil has no positive existence, and it is but a privation of good. The privation theory of good claims the opposite. I approach this topic as one element in the so-called evil-God Challenge. Stephen Law has argued that the epistemic support for belief in an omniscient, omnipotent, and morally perfect God (theism) is on a par with the epistemic support for belief in an omniscient, omnipotent, but completely evil-God (maltheism). In fact, he concludes, the arguments for an evil God are symmetrical with, and isomorphic to, those for a good God. The privation theory of evil has often been used to defend theism against the argument from evil. Thus, part of the evil-God Challenge is to evaluate arguments for the privation theory of evil for their vulnerability to maltheist parody. I consider a broad range of arguments for the privation theory of evil, and I argue that most of them are vulnerable to parodic neutralization. Furthermore, I argue that although the thesis of the convertibility of being and goodness is often held to entail the privation theory of evil, or to be entailed by it (or to be equivalent to it), it is independent of the privation theory. I do find that David Oderberg’s recent argument for the privation theory of evil resists any easy maltheist parody, but I argue that it has a defect. I sketch an argument according to which his good-as-fulfillment account is compatible with a perfectly evil god. My tentative conclusion is that the privation theory of evil enjoys little more plausibility than does the privation theory of good.